CLEO Pacific Rim Conference 2018
DOI: 10.1364/cleopr.2018.th3b.5
|View full text |Cite
|
Sign up to set email alerts
|

Controlled HHG with a Sub-Cycle mJ-Level Parametric Waveform Synthesizer

Abstract: We present high-harmonic generation (HHG) driven with a sub-cycle mJ-level parametric waveform synthesizer. The HHG yield and spectral shape can be controlled by varying the carrier-envelope phase and the relative phase in the synthesizer channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…On the basis of this scheme, in 2018, Rossi et al (32) boosted the energy of the light transients to nearly 1 mJ by using a 20-mJ, 1-kHz, 150-fs Ti:Sa amplifier to (i) generate multi-octave seed pulses and (ii) pump the two parallel OPCPA channels. In a follow-up experiment, Mainz et al (33) demonstrated the effect of the shape of the generated light transients on HHG yield. However, boosting the energy and average power of light transients beyond this value calls for a different frontend due to the limitations of simultaneous energy and power scalability in Ti:Sa amplifiers (34).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of this scheme, in 2018, Rossi et al (32) boosted the energy of the light transients to nearly 1 mJ by using a 20-mJ, 1-kHz, 150-fs Ti:Sa amplifier to (i) generate multi-octave seed pulses and (ii) pump the two parallel OPCPA channels. In a follow-up experiment, Mainz et al (33) demonstrated the effect of the shape of the generated light transients on HHG yield. However, boosting the energy and average power of light transients beyond this value calls for a different frontend due to the limitations of simultaneous energy and power scalability in Ti:Sa amplifiers (34).…”
Section: Introductionmentioning
confidence: 99%